Comparison between ultrasound guided erector spinae plane block and paravertebral block on acute and chronic post mastectomy pain after modified radical mastectomy: randomized controlled trial - Samy Abdelrahman Amr; Ahmed Hassan Othman; Eman Hassan Ahmed; Romany Gergis Naeem; Shereen Mamdouh Kamal (BMC Anesthesiology)
Abstract Background Inadequate acute postoperative pain management is linked to the effect on the stress response and development of chronic pain. A unique regional anaesthetic method that is becoming more important for postoperative pain management is erector spinea plane block (ESP). Since its initial description, physicians have questioned weather this novel easy method can take the place of paravertebral block (PVB). Our goal was to evaluate, in contrast to control group, the effects of ESP & PVB on acute and chronic post-mastectomy pain. Methods One hundred and five female patients undergoing modified radical mastectomy participated in this study, randomly allocated into three equal groups: erector spinae plane block (ESP), thoracic paravertebral (TPV), and control groups. Both blocks were ultrasound-guided with 20 ml 0.25% bupivacaine according to patients’ group, control group was administered standard general anaesthesia without intervention. Total morphine consumption in the first 24 h postoperative was the primary outcome. The secondary outcomes were time to the first analgesia, (Visual Analogue Scale)VAS score, serum level of cortisol and prolactin, sedation score, side effects, and LANSS scores in the first, third, and sixth postoperative months were among the variables compared between groups. Results Total morphine consumption in the first 24 h was significantly higher in control than ESP and TPV groups (10.74 ± 1.37, 8.17 ± 1.69, 5.70 ± 1.95 respectively p < 0.001). Time to first analgesic request was the shortest in control versus ESP and TPV groups as (4.37 ± 3.06, 8.13 ± 1.75, 10.64 ± 1.83 h respectively p ˂0.001). ESP and TPV had significantly lower cortisol and prolactin levels compared to control (p < 0.001). The highest LANSS scores were in the control group in the first, third, and sixth months compared with ESP and TPV, with no significant difference between ESP and TPV. Conclusion ESP and TPV blocks provided superior early postoperative analgesia and reduced stress response compared to the control group in female patients undergoing modified radical mastectomy. PVB is better than ESB in acute postoperative pain management (the total morphine consumption VAS score and time of first analgesic request). Both techniques showed better long-term outcomes compared to the control group regarding LANSS score in the 6-month follow-up. Trial registration https://www.ClinicalTrials.gov trial registry (identifier NCT04498234 on 04/08/2020).